Zagadnienia immunitetu przedsiebiorstw państwowych: [The problem of immunity of state enterprises] (Studia Prawnicze / The Legal Studies, 1967)
In the author’s view the state immunity in the field of jurisdiction and enfor- cment of judgments is not to be vested in state entreprises that function on the basis of economic calculus if heir personal law recognizes them as fully separated juridical persons with own property and independent liability. This law governs also the question whether immunity is to be vested in such an entreprise or not.Further on, the legal status of state entreprises in socialist countries is present- ed. The analysis made from the legal point of view leads the author to the conclu- sion that according to the law in these countries the mentioned (category of state entreprises does not take the advantage of state immunity.With regard to the requirements of international trade, it iis to be de- sired - in the author’s opinion - that the participating state entreprises be not protected by immunity, i.e. that the legal status of such a type for such state entreprises be accepted by all .countries. Renunciation from protecting state entreprises by state immunity is advantageous foir the „(business like” approach to the international trade what undoubtedly has beneficial effects.The decision whether courts of justice of a given country have jurisdiction or not rests with the law of this country. The conditions and the procedures of protective measures or enforcement of judgments are also subjected to the law of the country in which application for protection of enforcement is made.Next, the author discusses the problem of immunity of state entreprises in the legal science. Analysis of the subject schows that there is a tendency from doubts to negation verg existence of this immunity. It is to be seen particularly in the newest legal science in socialist countries.This problem in the aspect of adjudication in Western countries is the subject matter of the last section of the work.